The progressive in 19th and 20th century settler and indigenous Indian English. Issue 3 (24th April 2020) - Fuchs, Robert
Abstract: Based on a diachronic newspaper corpus, this study analyses change in the use of the progressive in the Indian English (IndE) settler strand and indigenous strand varieties from 1900 to 2000, comparing it to developments in British English (BrE). Results indicate that these three varieties showed distinct patterns of usage. The IndE indigenous strand reveals evidence of substrate transfer in the use of perfect progressives and unbounded/undelimited habitual progressives. Some of the resulting usage patterns appear to have been carried over to the IndE settler strand. Diachronically, similar developmental trends can be observed in IndE and BrE, although IndE was slower to adopt these trends ('colonial lag'). By contrast, linguistic features caused by substrate transfer decreased in frequency over time. Overall, diachronic developments do not indicate divergence between IndE and BrE, supporting the analysis of Indian English being in a 'steady state' instead of advancing to full endonormativity.